Total Oncology is necessary for Japanese new era - Tsuyoshi Shirakawa (Global Journal of Cancer Therapy - Peertechz Publications, 2018)
Still in Japan, medical oncologists need to play a main role and work a lot of tasks by themselves in cancer chemotherapy. The situation of cancer chemotherapy has progressed day by day and considering the current environment surrounding medical oncology, we must discuss what is necessary for and establish the new concept for medical oncology.